Managing Quality and Safety During the Production of Yoghurt with Honey Products - Merzlov, S.V.; Rudakova, T.V.; Snizhko, O.O.; Lomova, N.M.; Narizhniy, S.A.; Voroshchuk, V.Ya. (Science and Innovation, 2024)
Introduction. One of the innovative approaches to developing food quality and safety programs today is a system based on the principles of HACCP (Hazard Analysis Critical Control Points). The system enables to prevent danger in the early stages of food production. Problem Statement. In Ukraine, it is necessary to carry out a special monitoring of the quality and safety of dairy products due to a poor quality of raw materials and significant difficulties in tracing its use in the processing, which, together with the lack of refrigerated logistics and storage, significantly shorten the shelf life of Ukrainian dairy products as compared with the European ones. Purpose. The use of HACCP principles for developing new types of dairy products, in particular, yogurt with honey products. Materials and Methods. Dairy, biotechnological and non-dairy raw materials, packing material, stages of the technological process. Results. All possible hazardous factors that may exist in raw materials, packaging materials or during the use of any technological operation associated with the product haves been identified. The analysis of risks for each potentially dangerous factor during the production of yogurt with honey products has been carried out and a list of potential dangers based on the risk chart has been compiled. It has been established that the biological potentially dangerous factors include coliforms, pathogenic microbes, mold, and yeast; the chemical ones are toxic elements, radionuclides, mycotoxins, and antibiotics; the physical ones include impurities coming from raw materials, with water, from technological equipment and packaging materials. Six critical control points have been determined: the acceptance of dairy and non-dairy raw materials; cooling and redundancy of milk; pasteurization; fermentation; and packing. Conclusion. The technological chart for making yogurt with honey products by a reservoir method using the HACCP elements has been developed and the indicators of quality and safety of the finished product have been determined.